Feeding interactions for children with cerebral palsy: contributions of mothers' psychological state and children's skills and abilities - Welch, K; Pianta, R C; Marvin, R S; Saft, E W (Journal of developmental and behavioral pediatrics, 2000)
This study examined the relative importance of children's feeding skills and abilities and mothers' psychological state regarding their child's diagnostic status in predicting the observed quality of mother-child interaction during a naturalistic feeding situation. The study subjects were 69 children with cerebral palsy (CP), aged 14 to 53 months, and their mothers. Functional impairments of the children ranged from mild to severe. Mother-child interaction was observed during 20 minutes of feeding and was scored using global ratings of mothers' and children's socioemotional behavior. In addition, mothers' feeding interactions were dichotomously coded for sensitive and responsive behaviors. Children's feeding skills and abilities were assessed by maternal report and by observation. Mothers' resolution of grief associated with the child's diagnosis was assessed using standardized interview procedures. The findings strongly indicate that, contrary to expectations, the mothers' resolution status was not related to qualities of the feeding interactions (either dyadic or mothers' behavior) and that feeding interactions are best predicted for children with CP by their skills and abilities. The results are discussed in relation to the nature, determinants, and consequences of feeding in children with and without disabilities.